Female Human Capital Mismatch: An extension for the British public sector - Yannis Galanakis (Global Labor Organization (GLO), 2020)
This paper looks at the extent of labour market mismatch of public-sector female employees. It contributes to earlier findings for the British labour market by taking into account the endogenous self-selection into jobs. Estimates are based on data from the British Household Panel Study and the 'Understanding Society' covering the years 1991-2016. The analysis verifies that the public sector offers a few lowskilled jobs and employs, mostly, high-educated (female) workers. Regarding the market flows, findings show the greater mobility of the female workforce, which moves proportionately between sectors. Greater in-/out-flows to/from private sector are observed regardless the gender of the employee. Once comparing women to the median employee, a sizeable incidence of mismatch arises due to negative selection. Specifications using the selection model for the public sector illustrate a systematically higher magnitude of mismatch. Pooled results seem to dominate when women seen in the male labour market or in a restricted subsample. Finally, the map of occupations in mismatch supports that the public sector is more attractive as a waiting room for highly-qualified graduates. They queue less time until they find a good job. Hence, policy implications regarding the allocation of jobs for women may arise.
Keywords: I24; I26; J21; J24; 330; Human Capital Mismatch; women; British public-sector